Analysis of Growth Patterns of Islamic Boarding School Business Architecture - Granita, Selvi Dwi; Kristi, Vika Anindya; Asyarofi, Sonia Desy; Yaqin, Muhammad Ainul (Proceeding International Conference on Science and Engineering, 2020)
The growth pattern of boarding schools is the process of growing boarding schools from the simplest type to the highest type so as to produce more complex business processes. The growth of business processes can affect the growing needs of Islamic boarding schools. Currently there is no modeling of the growth patterns of Islamic boarding schools, so that the needs of Islamic boarding schools have not been well predicted. Therefore, an analysis of the growth patterns of business architecture in Islamic boarding schools is made so that the growth of Islamic boarding school business architecture can be well predicted. Analysis of the growth pattern of the business architecture of this Islamic boarding school uses cellular automata analysis methods. The parameter that triggers growth is the number of students, from this number can trigger other growth such as the number of teachers, the number of dormitories, the number of staff and several other supporting facilities. The final results obtained from this study are a form of growth patterns in boarding school business architecture represented in the form of graphs that can provide information to be used as academic guidelines in the growth of boarding school business architecture needs.